Elements of style : designing a home & a life - Gates, Erin T. (Simon & Schuster, 2014)
"From the rising-star designer and author of the hit blog, Elements of Style, a full-color, fully illustrated book packed with honest advice, inspiration, ideas, and lessons learned about designing a home that reflects your personality and style. Elements of Style is a uniquely personal and practical decorating guide that shows how designing a home can be an outlet of personal expression and an exercise in self-discovery. Drawing on her ten years of experience in the interior design industry, Erin combines honest design advice and gorgeous professional photographs and illustrations with personal essays about the lessons she has learned while designing her own home and her own life--the first being: none of our homes or lives is perfect. Like a funny best friend, she reveals the disasters she confronted in her own kitchen renovation, her struggles with anorexia, her epic fight with her husband over a Lucite table, and her secrets for starting a successful blog. Organized by rooms in the house, Elements of Style invites readers into Erin's own home as well as homes she has designed for clients. Fresh, modern, and colorful, it is brimming glamour and style as well as advice on practical matters from choosing kitchen counter materials to dressing a bed with pillows, picking a sofa, and decorating a nursery without cartoon characters. You'll also find a charming foreword by Erin's husband, Andrew, and an extensive Resource and Shopping Guide that provides an indispensable a roadmap for anyone embarking on their first serious home decorating adventure. With Erin's help, you can finally make your house your home"--Resumé vydavatele
Keywords: dekorace interiérů; bytové interiéry; bytové vybavení; interior decoration; residential interiors; house furnishings; příručky; handbooks and manuals